1994
DOI: 10.1016/0014-5793(94)00769-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of protein kinase Cα and its free catalytic subunit, protein kinase M, in intact human neuroblastoma cells and under cell‐free conditions

Abstract: Proteolytic cleavage of protein kinase C (PKC) under cell-free conditions generates a co-factor independent, free catalytic subunit (PKM). However, the difficulty in visualizing PKM in intact cells has generated controversy regarding its physiological relevance. In the present study, treatment of SH-SY-5Y cells with 2-O-tetradecanoylphorbol 13-acetate resulted in complete down-regulation of PKC within 24 h without detection of PKM. By contrast, low levels of PKM were transiently detected following ionophore-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…However, the results gained from a number of experiments failed to reveal a particular combination of treatments whereby a catalytic fragment of Apl I or Apl II could be reliably detected by Western blotting under our conditions. Several other studies have likewise reported that endogenous generation of PKM is very difficult to detect (Shea et al, 1994), and a failure to observe PKM by immunoblotting is not uncommon (Grünbaum Figure 5. Calphostin C, a PKC inhibitor interacting with the regulatory domain, blocks the induction but not the maintenance of site-specific ITM.…”
Section: Aplysia Pkc Isoforms Are Proteolyzed By Calpainmentioning
confidence: 96%
“…However, the results gained from a number of experiments failed to reveal a particular combination of treatments whereby a catalytic fragment of Apl I or Apl II could be reliably detected by Western blotting under our conditions. Several other studies have likewise reported that endogenous generation of PKM is very difficult to detect (Shea et al, 1994), and a failure to observe PKM by immunoblotting is not uncommon (Grünbaum Figure 5. Calphostin C, a PKC inhibitor interacting with the regulatory domain, blocks the induction but not the maintenance of site-specific ITM.…”
Section: Aplysia Pkc Isoforms Are Proteolyzed By Calpainmentioning
confidence: 96%
“…PKC activity is also determined by its degradation. The literature indicates that the calcium-lipid-dependent protease calpain-can degrade PKC to a catalytically active PKM by cleaving off the regulatory domain (43,46,154,161). PKM may be a constitutively active enzyme that mediates long-term phosphorylation activity of PKC.…”
Section: The Basics Of Pkcmentioning
confidence: 99%
“…41 ± 43 Calpain cleaves activated PKC at the hinge region between the regulatory and catalytic domain and cleaved PKC is subsequently rapidly degraded by other cellular proteases. 44 This process, known as`downregulation' functions to attenuate the PKC signal, thus preventing the persistent accumulation of activated kinases. Our data indicates that activation of PKC with low doses of TPA results in a modest induction of apoptosis as indicated by DNA fragmentation and caspase-3 activation.…”
Section: Blocking Degradation Of Activated Pkc Enhances Tpa-induced Amentioning
confidence: 99%